Selective removal of Zr(IV) from simulated High-Level liquid waste of metallic fuel reprocessing using hydroxyacetamide Extractant: Insights from solvent extraction and density functional theory computations. (1st November 2021) - Prathibha, T.; Suneesh, A.S.; Chandra, Swaroop; Sriram, S.; Ramanathan, N.
Graphical abstract: The focus of the present paper is the selective separation of Zr(IV) from simulated HLLW solutions using DOHyA extractant in n -dodecane. The present separation process involves three stages such as extraction, scrubbing of other fission products and stripping and recovery of Zr(IV). As a result, the flow chart for the separation of Zr(IV) is also established. The complexation behaviour of Zr(IV) at the various stages of extraction and stripping with the aid of DFT calculations is accomplished. Abstract: A liquid-liquid extraction method for the separation of Zr(IV) from simulated high-level liquid waste (SHLLW) solutions using N, N -di-octyl-2-hydroxyacetamide (DOHyA) was studied. The method was found to be applicable for the recovery of Zr(IV) from conventional SHLLW solutions as well as the SHLLW solutions from metallic fuel reprocessing streams containing Zr(IV) up to 8 g/L. DOHyA showed quantitative extraction of Zr(IV) from all the simulated waste solutions, along with co-extraction of other fission products and Am(III). Excluding Zr(IV) and Mo(VI), all the other co-extracted metal ions were efficiently scrubbed from the loaded DOHyA solvent using 0.5 M or 1 M nitric acid. The selective stripping of Zr(IV) that remained in the solvent phase was subsequently accomplished using 0.2 M oxalic acid solution. The complexation behaviour of Zr(IV) with DOHyA was investigated using Density Functional Theory ( DFT ) calculations, which divulged the geometry and stability of Zr-DOHyA-HNO3 and Zr(C2 O4 )2 complexes formed under the extraction and stripping conditions. With the aid of quantum theory of atoms in molecules, natural bond orbital and non-covalent interaction analyses, the rationale behind the selective removal of Zr(IV) from SHLLW using DOHyA extractant was clearly unravelled.